A photocatalytic self-cleaning hamburger structure nanofiber membrane for protein separation
Patent Information
- Application Number
- CN202410688284.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-30
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-05-30
AI Technical Summary
现有膜分离技术在分离生物发酵液时容易被污染,无法满足高效分离和稳定运行的要求。
A photocatalytic self-cleaning hamburger-structured nanofiber membrane was prepared by microfluidic electrospinning. C3N4 modifier and polyphenol modifier were introduced by blending modification to form a three-layer functionalized fiber layer, which improved the hydrophilicity and antifouling properties of the membrane.
A high-throughput, high-oil-retention, and high-protein-permeability nanofiber membrane has been developed, which is suitable for the separation and purification of complex biological fermentation broths and has good long-term stability.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to a photocatalytic self-cleaning hamburger-structured nanofiber membrane for protein separation, belonging to the field of separation membrane preparation technology. This nanofiber membrane has advantages such as high pure water flux, good oil retention performance, good permeability for small molecule proteins, and excellent light response effect, and is suitable for the field of protein separation and purification. Background Technology
[0002] While modern bio-fermentation technology is widely used, separating the various components in fermentation broth remains a significant challenge. Traditional techniques such as gravity, centrifugation, and flotation can cause secondary pollution and are limited to simple bio-fermentation broth separations. In contrast, membrane separation technology is gradually becoming mainstream. Among these, microfluidic electrospinning for the preparation of high-porosity, small-pore separation membranes shows broad application prospects. Microfluidic electrospinning is the main method for the large-scale preparation of nanofiber membranes. In recent years, the use of microfluidic electrospinning to prepare nanofiber membranes for protein separation and purification processes has developed rapidly. These polymer membranes possess excellent hydrophobicity, chemical stability, thermal stability, and good processability.
[0003] Currently, research has been conducted both domestically and internationally on the oil-water retention and protein permeation effects of nanofiber membranes during the separation process. Patent CN202211609351.3 discloses a biomimetic photocatalytic self-cleaning oil-water separation membrane with a moth-eye structure and its preparation method. This membrane exhibits superhydrophilicity and underwater superoleophobicity, with a pure water flux of 3900-7000 L·m⁻¹. -2 ·h -1 The separation membrane has a light absorption rate of over 95% and good self-cleaning effect. Patent CN202211361463.1 invented a light-driven single-layer Janus oil-water separation membrane and its preparation method. This membrane preparation process is simple, efficient, and environmentally friendly, with a pure water flux of 3500-6000 L·m⁻². -2 ·h -1 It exhibits good photoreactivity and high flux recovery rate. In comparison, the photocatalytic self-cleaning high-flux functionalized hamburger-structured nanofiber membrane for protein separation and purification prepared in this invention possesses a higher pure water flux (15000-19000 L·m⁻¹). -2 ·h -1 It has a stable flux recovery rate (95%-100%) after self-cleaning operation, the membrane preparation process is simple and reliable, and it has good oil and water rejection rate and excellent protein permeability for complex bio-fermentation broth systems.
[0004] This invention relates to a photocatalytic self-cleaning hamburger-structured nanofiber membrane for protein separation. This nanofiber membrane has advantages such as high pure water flux, good oil retention, good permeability for small molecule proteins, and excellent light response. It is suitable for the field of protein separation and purification and can be applied to complex separation systems such as bio-fermentation broth separation. Summary of the Invention
[0005] The purpose of this invention is to address the current problem of membranes being easily fouled and unable to meet the requirements of membrane separation. A photocatalytic self-cleaning hamburger-structure nanofiber membrane for protein separation has been prepared. The hydrophilic modified nanofiber membrane prepared by this method has advantages such as high flux, good oil retention, and good protein permeation. It is suitable for membrane separation of bio-fermentation broth processes and can ensure excellent separation effect and long-term stable operation.
[0006] The photocatalytic self-cleaning high-throughput functionalized hamburger-structured nanofiber membrane for protein separation and purification prepared by this invention is produced by first modifying the nanofiber through a blending method, and then preparing the spinning solution using a microfluidic electrospinning method, including the following steps: Step 1): The synthesis steps of C3N4 modifier are as follows: Weigh 20-40 g of nitrogen-containing organic matter and place it in a 150-250 ml covered alumina crucible. In a muffle furnace, heat the mixture at 6-10 ℃ for 1 minute. -1 The heating rate was increased to 550-650℃ in air atmosphere and held for 2-6 h. After calcination, the mixture was cooled to room temperature to obtain a light yellow C3N4. The C3N4 powder was then thoroughly ground in an agate mortar and finally obtained as a light yellow C3N4 powder, which was then sealed and stored for later use.
[0007] Step 2): Preparation of the spinning solution: The spinning solution is prepared from three materials according to the following component mass percentages: First material: 11-15% base material, 6-10% TPU, and the remainder is solvent. Dissolve the base material in the solvent, heat and stir. After dissolving, add the TPU and continue stirring for 3-5 hours until completely dissolved. Second material: 11-15% base material, 6-10% TPU, 0.6-1% polyphenol modifier, and the remainder is solvent. Dissolve the polyphenol modifier in the solvent, heat and stir. After dissolving, add the base material and TPU, and continue heating and stirring for 1.5-3.5 hours until completely dissolved. Third material: 11-15% base material, 6-10% TPU, 0.1-0.5% C3N4, and the remainder is solvent. Dissolve the C3N4 in the solvent, heat and stir. After dissolving, add the base material and TPU, and continue heating and stirring for 1.5-3.5 hours until completely dissolved.
[0008] Step 3) Preparation of modified membrane: Preparation of photocatalytic self-cleaning high-throughput functionalized hamburger structure nanofiber membrane for protein separation and purification: The spinning solution in step (1) was spun into a membrane using microfluidic electrospinning. The DC voltage of the spinning machine was set to 16-20 KV, the flow rate of the injection pump was 1.1-1.5 ml / h, and the receiving distance was 16-20 cm. The membrane fabrication process involves the sequential spinning of three materials. The first material, 4-6 ml, is spun for 3-5 hours to form a nanofiber substrate membrane with a thickness of 55-75 μm. Then, a second material, 2-4 ml, is rapidly spun on the pre-formed membrane for 1.5-3.5 hours to form a polyphenol-modified nanofiber membrane with a thickness of 90-130 μm. Similarly, a third material, 2-4 ml, is spun for 1.5-3.5 hours to form a polyphenol-g-C3N4 nanofiber membrane with a total thickness of 110-145 μm and a pore size of 0.3-0.8 μm.
[0009] Step 4) Evaluation of photocatalytic self-cleaning performance: After protein separation cycle, the membrane is placed in 1-5 wt.% sodium sulfate solution and stirred. At the same time, it is subjected to photocatalytic degradation of surface organic matter under 100-750 W xenon lamp irradiation for 0.5-2.5 h. After degradation, the membrane's pure water flux recovery rate and macromolecular oil rejection rate are tested.
[0010] Preferably, the calcination time of the nitrogen-containing organic matter in step 1) is 2-6 h.
[0011] Preferably, the material used to synthesize the nitrogen-containing organic compound in step 1) is one or more of melamine, thiourea, dicyandiamine, and urea.
[0012] Preferably, the substrate selected in step 2) is one of polyvinylidene fluoride, polyethersulfone, and polyacrylonitrile.
[0013] Preferably, the polyphenol modifier in step 2) is one or more of tea polyphenols, pyrogallol, and tannic acid.
[0014] Preferably, the solvent in step 2) can be one of N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, or N-methylpyrrolidone.
[0015] This invention provides a photocatalytic self-cleaning hamburger-structured nanofiber membrane for protein separation, characterized in that the pure water flux of the functionalized hamburger-structured nanofiber membrane is 15000-19000 L·m⁻¹. -2 ·h -1The membrane exhibits a high oil retention rate (≥99.4%), demonstrating significant oil removal efficiency. It also achieves a bovine serum albumin (68 KD) permeability (≥88%), a pepsin (35 KD) permeability (≥95.9%), and a peptide (≤25 KD) permeability (100%), demonstrating remarkable effectiveness in separating bio-fermentation broth. Even after protein separation cycles, this functionalized hamburger-structured nanofiber membrane maintains excellent oil retention and protein permeability while retaining a high pure water flux, making it suitable for a wide range of applications in bio-fermentation broths.
[0016] Description of the invention principle: This invention prepares a photocatalytic self-cleaning hamburger-structured nanofiber membrane for protein separation. The base membrane, photocatalytic self-cleaning functional layer, and high-flux functional layer are integrated into one using microfluidic electrospinning. First, the base membrane layer serves as the support layer, forming the main body of the membrane and ensuring its mechanical strength and toughness. Second, a polyphenolic modifier is introduced, and its excellent hydrophilicity contributes to the high-flux functional layer, significantly increasing the flux of the nanofiber membrane. Finally, the addition of the photocatalytic modifier C3N4 not only enables self-cleaning but also greatly increases the membrane's antifouling properties. The combination of these three functionalized fiber layers, with their diverse membrane channels, significantly increases the membrane's retention rate for oil-water emulsions.
[0017] Beneficial effects: Compared with existing technologies, this invention modifies the membrane through a continuous multi-step microfluidic electrospinning method. The modified monomers are dissolved in the spinning solution, significantly improving its stability. By repeatedly spinning, spun membranes with different gradients are obtained, resulting in modified nanofiber membranes with high flux, good oil and dirt retention, good protein permeability, and good long-term stability, suitable for the separation and purification of bio-fermentation broths. The introduction of polyphenol modifiers and C3N4 modifiers into the substrate enhances its hydrophilicity while improving its antifouling performance through photocatalytic reaction, thus ensuring the long-term stability of the membrane. Attached Figure Description
[0018] Figure 1 Example 1 of the present invention: The first material spinning solution for the nanofiber membrane Figure 2 Example 2 of the present invention: The second material spinning solution for the nanofiber membrane Figure 3 Example 3 of the present invention: The third material spinning solution for nanofiber membranes Figure 4 Scanning electron microscope image of the first layer surface of the nanofiber membrane in Example 1 of this invention Figure 5 Scanning electron microscope image of the second layer surface of the nanofiber membrane in Example 2 of this invention. Figure 6Scanning electron microscope image of the third layer surface of the nanofiber membrane in Example 3 of this invention. Figure 7 Cross-sectional scanning electron microscope image of the nanofiber membrane in Example 4 of this invention Figure 8 Cross-sectional scanning electron microscope image of the nanofiber membrane in Example 5 of this invention. Detailed Implementation
[0019] The present invention will be further described below with reference to specific embodiments.
[0020] Example 1 Step 1): The synthesis steps of C3N4 modifier are as follows: Accurately weigh 20 g of melamine and place it in a 150 ml covered alumina crucible. In a muffle furnace, heat at 6 ℃ for 1 min. -1 The heating rate was increased to 550 °C in air atmosphere and held for 2 h. After calcination, the mixture was cooled to room temperature to obtain pale yellow C3N4. The powder was then thoroughly ground in an agate mortar to obtain pale yellow C3N4 powder, which was then sealed and stored for later use.
[0021] Step 2): The spinning solution is prepared from three materials according to the following component mass percentages: First material: 11% base material, 6% TPU, and the remainder is solvent. Dissolve the base material in the solvent, heat and stir. After dissolving, add the TPU and continue stirring for 3 hours until completely dissolved. Second material: 11% base material, 6% TPU, 0.6% polyphenol modifier, and the remainder is solvent. Dissolve the polyphenol modifier in the solvent, heat and stir. After dissolving, add the base material and TPU, and continue heating and stirring for 1.5 hours until completely dissolved. Third material: 11% base material, 6% TPU, 0.1% C3N4, and the remainder is solvent. Dissolve the C3N4 in the solvent, heat and stir. After dissolving, add the base material and TPU, and continue heating and stirring for 1.5 hours until completely dissolved.
[0022] Step 3) Preparation of modified membrane: Preparation of photocatalytic self-cleaning functionalized hamburger structure nanofiber membrane for protein separation and purification: The spinning solution in step (1) was spun into a membrane using microfluidic electrospinning. The DC voltage of the spinning machine was set to 16 KV, the flow rate of the injection pump was 1.1 ml / h, and the receiving distance was 16 cm. The membrane preparation process involved three materials being spun sequentially. The first material was 4 ml, and the nanofiber substrate was spun for 3 h to form a membrane with a thickness of 55 μm. Then, the second 2 ml of spinning solution was quickly spun on the already formed membrane to form a polyphenol modified nanofiber membrane, and the two membrane layers were 90 μm thick. Similarly, the third material was 2 ml, and the polyphenol-g-C3N4 nanofiber membrane was spun for 1.5 h to form a polyphenol-g-C3N4 nanofiber membrane with a total membrane thickness of 115 μm and a membrane pore size of 0.3-0.8 μm.
[0023] Step 4) Evaluation of photocatalytic self-cleaning performance: After undergoing a protein separation cycle experiment, the membrane was placed in a 1 wt.% sodium sulfate solution and stirred. At the same time, it was subjected to photocatalytic degradation of surface organic matter under a 100 W xenon lamp for 0.5 h. After degradation, the membrane's pure water flux recovery rate and macromolecular oil rejection rate were tested.
[0024] The pure water flux of the composite membrane is 15500 L·m -2 ·h -1 The protein exhibited excellent permeability for proteins, demonstrating a high efficiency in separating bio-fermentation broth. After a protein separation cycle experiment, and subsequent self-cleaning operation under a 100 W xenon lamp, the pure water flux recovery rate was 95.4% after 0.5 h of illumination. The high molecular weight oil rejection rate was 98.8%, the bovine serum albumin permeability was ≥89.2%, and the pepsin permeability was ≥97.3%. The results showed a 99.5% rejection rate for macromolecular oils, a ≥88.8% permeability for bovine serum albumin, and a ≥97.3% permeability for pepsin.
[0025] Example 2 Step 1): The synthesis steps of C3N4 modifier are as follows: Accurately weigh 25 g of melamine and place it in a 200 ml covered alumina crucible. In a muffle furnace, heat at 7 ℃ for 1 min. -1 The heating rate was increased to 580 °C in air atmosphere and held for 3 h. After calcination, the mixture was cooled to room temperature to obtain a light yellow C3N4. The C3N4 was then thoroughly ground in an agate mortar to obtain a light yellow C3N4 powder, which was then sealed and stored for later use.
[0026] Step 2): The spinning solution is prepared from three materials according to the following component mass percentages: First material: 12% base material, 7% TPU, and the remainder is solvent. Dissolve the base material in the solvent, heat and stir. After dissolving, add the TPU and continue stirring for 3.5 hours until completely dissolved. Second material: 12% base material, 7% TPU, 0.7% polyphenol modifier, and the remainder is solvent. Dissolve the polyphenol modifier in the solvent, heat and stir. After dissolving, add the base material and TPU, and continue heating and stirring for 2 hours until completely dissolved. Third material: 12% base material, 7% TPU, 0.2% C3N4, and the remainder is solvent. Dissolve the C3N4 in the solvent, heat and stir. After dissolving, add the base material and TPU, and continue heating and stirring for 2 hours until completely dissolved.
[0027] Step 3) Preparation of modified membrane: Preparation of photocatalytic self-cleaning functionalized hamburger structure nanofiber membrane for protein separation and purification: The spinning solution in step (1) was spun into a membrane using microfluidic electrospinning. The DC voltage of the spinning machine was set to 17 KV, the flow rate of the injection pump was 1.2 ml / h, and the receiving distance was 17 cm. The membrane preparation process involved three strands of material being spun sequentially. The first strand of material was 4.5 ml, and the nanofiber substrate was spun for 3.5 h to form a membrane with a thickness of 60 μm. Then, the second strand of spinning solution of 2.5 ml was quickly spun on the membrane to form a polyphenol modified nanofiber membrane for 2 h, with a two-layer membrane thickness of 105 μm. Similarly, the third strand of material was 2.5 ml, and the polyphenol-g-C3N4 nanofiber membrane was spun for 2 h to form a polyphenol-g-C3N4 nanofiber membrane with a total membrane thickness of 125 μm and a membrane pore size of 0.3-0.8 μm.
[0028] Step 4) Evaluation of photocatalytic self-cleaning performance: After undergoing a protein separation cycle experiment, the membrane was placed in a 2 wt.% sodium sulfate solution and stirred. At the same time, it was subjected to photocatalytic degradation of surface organic matter under a 150 W xenon lamp for 1 h. After degradation, the membrane's pure water flux recovery rate and macromolecular oil rejection rate were tested.
[0029] The composite membrane has a pure water flux of approximately 16300 L·m⁻¹. -2 ·h -1 The protein exhibited excellent permeability for proteins, demonstrating a high efficiency in separating bio-fermentation broth. After a protein separation cycle experiment, a self-cleaning process was performed using a 150 W xenon lamp. After 1 hour of illumination, the pure water flux recovery rate was 96.6%, the macromolecular oil rejection rate was 98.9%, the bovine serum albumin permeability was ≥90.3%, and the pepsin permeability was ≥97.2%. The high permeability for macromolecular oils was 99.4%, the bovine serum albumin permeability was ≥90.3%, and the pepsin permeability was ≥97.2%.
[0030] Example 3 Step 1): The synthesis steps of C3N4 modifier are as follows: Accurately weigh 30 g of melamine and place it in a 200 ml covered alumina crucible. In a muffle furnace, heat at 8 ℃ for 1 min. -1 The heating rate was set at 600 °C in air and maintained for 4 h. After calcination, the mixture was cooled to room temperature to obtain a pale yellow C3N4. The C3N4 was then thoroughly ground in an agate mortar to obtain a pale yellow C3N4 powder, which was then sealed and stored for later use.
[0031] Step 2): The spinning solution is prepared from three materials according to the following component mass percentages: First material: 13% base material, 8% TPU, and the remainder is solvent. Dissolve the base material in the solvent, heat and stir. After dissolving, add the TPU and continue stirring for 4 hours until completely dissolved. Second material: 13% base material, 8% TPU, 0.8% polyphenol modifier, and the remainder is solvent. Dissolve the polyphenol modifier in the solvent, heat and stir. After dissolving, add the base material and TPU, and continue heating and stirring for 2.5 hours until completely dissolved. Third material: 13% base material, 8% TPU, 0.3% C3N4, and the remainder is solvent. Dissolve the C3N4 in the solvent, heat and stir. After dissolving, add the base material and TPU, and continue heating and stirring for 2.5 hours until completely dissolved.
[0032] Step 3) Preparation of modified membrane: Preparation of photocatalytic self-cleaning functionalized hamburger structure nanofiber membrane for protein separation and purification: The spinning solution in step (1) was spun into a membrane using microfluidic electrospinning. The DC voltage of the spinning machine was set to 18 KV, the flow rate of the injection pump was 1.3 ml / h, and the receiving distance was 18 cm. The membrane preparation process involved three strands of material being spun sequentially. The first strand of material was 5 ml, and the nanofiber substrate was spun for 4 h to form a membrane with a thickness of 65 μm. Then, the second strand of spinning solution of 3 ml was quickly spun on the already formed membrane to form a polyphenol modified nanofiber membrane for 2.5 h, with a two-layer membrane thickness of 115 μm. Similarly, the third strand of material was 3 ml, and the polyphenol-g-C3N4 nanofiber membrane was spun for 2.5 h to form a polyphenol-g-C3N4 nanofiber membrane with a total membrane thickness of 135 μm and a membrane pore size of 0.3-0.8 μm.
[0033] Step 4) Evaluation of photocatalytic self-cleaning performance: After undergoing a protein separation cycle experiment, the membrane was placed in a 3 wt.% sodium sulfate solution and stirred. At the same time, it was subjected to photocatalytic degradation of surface organic matter under a 350 W xenon lamp for 1.5 h. After degradation, the membrane's pure water flux recovery rate and macromolecular oil rejection rate were tested.
[0034] The composite membrane has a pure water flux of approximately 17110 L·m⁻¹ -2 ·h -1 The protein exhibited excellent permeability for proteins, demonstrating a high efficiency in separating bio-fermentation broth. After a protein separation cycle experiment, photocatalytic reaction was performed under a 350 W xenon lamp. After 1.5 h of illumination, the pure water flux recovery rate was 97.3%, the macromolecular oil rejection rate was 99.3%, the bovine serum albumin permeability was ≥89.4%, and the pepsin permeability was ≥96.4%. The large molecular oil rejection rate was 99.3%, the bovine serum albumin permeability was ≥89.4%, and the pepsin permeability was ≥96.4%.
[0035] Example 4 Step 1): The synthesis steps of C3N4 modifier are as follows: Accurately weigh 35 g of melamine and place it in a 250 ml covered alumina crucible. In a muffle furnace, heat at 9 ℃ for 1 min. -1 The heating rate was increased to 625 °C in air atmosphere and held for 5 h. After calcination, the mixture was cooled to room temperature to obtain a light yellow C3N4. The C3N4 was then thoroughly ground in an agate mortar to obtain a light yellow C3N4 powder, which was then sealed and stored for later use.
[0036] Step 2): The spinning solution is prepared from three materials according to the following component mass percentages: First material: 14% base material, 9% TPU, and the remainder is solvent. Dissolve the base material in the solvent, heat and stir. After dissolving, add the TPU and continue stirring for 4.5 hours until completely dissolved. Second material: 14% base material, 9% TPU, 0.9% polyphenol modifier, and the remainder is solvent. Dissolve the polyphenol modifier in the solvent, heat and stir. After dissolving, add the base material and TPU, and continue heating and stirring for 3 hours until completely dissolved. Third material: 14% base material, 9% TPU, 0.4% C3N4, and the remainder is solvent. Dissolve the C3N4 in the solvent, heat and stir. After dissolving, add the base material and TPU, and continue heating and stirring for 3 hours until completely dissolved.
[0037] Step 3) Preparation of modified membrane: Preparation of photocatalytic self-cleaning functionalized hamburger structure nanofiber membrane for protein separation and purification: The spinning solution in step (1) was spun into a membrane using microfluidic electrospinning. The DC voltage of the spinning machine was set to 19 KV, the flow rate of the injection pump was 1.4 ml / h, and the receiving distance was 19 cm. The membrane preparation process involved three strands of material being spun sequentially. The first strand of material was 5.5 ml, and the nanofiber substrate was spun for 4.5 h to form a membrane with a thickness of 70 μm. Then, the second strand of spinning solution of 3.5 ml was quickly spun on the membrane to form a polyphenol modified nanofiber membrane for 3 h, with a two-layer membrane thickness of 125 μm. Similarly, the third strand of material was 3.5 ml, and the polyphenol-g-C3N4 nanofiber membrane was spun for 3 h to form a polyphenol-g-C3N4 nanofiber membrane with a total membrane thickness of 140 μm and a membrane pore size of 0.3-0.8 μm.
[0038] Step 4) Evaluation of photocatalytic self-cleaning performance: After undergoing a protein separation cycle experiment, the membrane was placed in a 4 wt.% sodium sulfate solution and stirred. At the same time, it was subjected to photocatalytic degradation of surface organic matter under a 500 W xenon lamp for 2 h. After degradation, the membrane's pure water flux recovery rate and macromolecular oil rejection rate were tested.
[0039] The composite membrane has a pure water flux of approximately 18190 L·m⁻¹ -2 ·h -1The study showed a high permeability rate for macromolecular oils (99.6%), bovine serum albumin (68 KD) permeability (≥89.3%), pepsin (35 KD) permeability (≥96.0%), and polypeptides (≤25 KD) permeability (100%), demonstrating excellent permeability for proteins and significant effectiveness in separating bio-fermentation broth. After a protein separation cycle experiment, photocatalytic reaction was conducted under a 500 W xenon lamp. After 2 hours of illumination, the pure water flux recovery rate was 98.5%, the macromolecular oil retention rate was 99.0%, the bovine serum albumin permeability was ≥89.4%, and the pepsin permeability was ≥96.2%.
[0040] Example 5 Step 1): The synthesis steps of C3N4 modifier are as follows: Accurately weigh 40 g of melamine and place it in a 250 ml covered alumina crucible. In a muffle furnace, heat at 10 °C for 1 min. -1 The heating rate was increased to 650 °C in air atmosphere and held for 6 h. After calcination, the mixture was cooled to room temperature to obtain a light yellow C3N4. The C3N4 was then thoroughly ground in an agate mortar to obtain a light yellow C3N4 powder, which was then sealed and stored for later use.
[0041] Step 2): The spinning solution is prepared from three materials according to the following component mass percentages: First material: 15% base material, 10% TPU, and the remainder is solvent. Dissolve the base material in the solvent, heat and stir. After dissolving, add the TPU and continue stirring for 5 hours until completely dissolved. Second material: 15% base material, 10% TPU, 1% polyphenol modifier, and the remainder is solvent. Dissolve the polyphenol modifier in the solvent, heat and stir. After dissolving, add the base material and TPU, and continue heating and stirring for 3.5 hours until completely dissolved. Third material: 15% base material, 10% TPU, 0.5% C3N4, and the remainder is solvent. Dissolve the C3N4 in the solvent, heat and stir. After dissolving, add the base material and TPU, and continue heating and stirring for 3.5 hours until completely dissolved.
[0042] Step 3) Preparation of modified membrane: Preparation of photocatalytic self-cleaning functionalized hamburger structure nanofiber membrane for protein separation and purification: The spinning solution in step (1) was spun into a membrane using microfluidic electrospinning. The DC voltage of the spinning machine was set to 20 KV, the flow rate of the injection pump was 1.5 ml / h, and the receiving distance was 20 cm. The membrane preparation process involved three strands of material being spun sequentially. The first strand of material was 6 ml, and the nanofiber substrate was spun for 5 h to form a membrane with a thickness of 75 μm. Then, the second strand of spinning solution of 4 ml was quickly spun on the already formed membrane to form a polyphenol modified nanofiber membrane for 3.5 h, with a two-layer membrane thickness of 130 μm. Similarly, the third strand of material was 4 ml, and the polyphenol-g-C3N4 nanofiber membrane was spun for 3.5 h to form a polyphenol-g-C3N4 nanofiber membrane with a total membrane thickness of 145 μm and a membrane pore size of 0.3-0.8 μm.
[0043] Step 4) Evaluation of photocatalytic self-cleaning performance: After undergoing a protein separation cycle experiment, the membrane was placed in a 5 wt.% sodium sulfate solution and stirred. At the same time, it was subjected to photocatalytic degradation of surface organic matter under a 750 W xenon lamp for 2.5 h. After degradation, the membrane's pure water flux recovery rate and macromolecular oil rejection rate were tested.
[0044] The composite membrane has a pure water flux of approximately 18400 L·m⁻¹. -2 ·h -1 The large molecular weight oil rejection rate was 99.4%, the permeability of bovine serum albumin (68 KD) was ≥89.0%, the permeability of pepsin (35 KD) was ≥96.1%, and the permeability of polypeptides (≤25 KD) was 100%, demonstrating excellent permeability for proteins and a significant effect on separating bio-fermentation broth. After a protein separation cycle experiment, photocatalytic reaction was carried out under a 750 W xenon lamp. After 2.5 h of illumination, the pure water flux recovery rate was 100%, the large molecular weight oil rejection rate was 99.2%, the permeability of bovine serum albumin was ≥88.3%, and the permeability of pepsin was ≥96.9%.
[0045] Table 1. Comparison of pure water flux, macromolecular oil rejection rate, and protein permeation rate between the present invention and currently published membranes.
[0046] Literature / Patent Sources [1] A porous solvent-cast film without a dense epidermis, its preparation method and application. Chinese Patent: CN117384420A. 2023.01.12 [2] A superhydrophilic self-cleaning oil-water separation membrane, its preparation method and application. Chinese Patent: CN109847598A. 2019.01.28 [3] A method for preparing a biomimetic photocatalytic self-cleaning oil-water separation membrane with a moth-eye structure. Chinese Patent: CN202211609351.3.2022.12.14 [4] A light-driven monolayer Janus oil-water separation membrane and its preparation method. Chinese Patent: CN202211361463.1.2022.10.31.
Claims
1. A method for preparing a photocatalytic self-cleaning hamburger-structured nanofiber membrane for protein separation, characterized in that, The photocatalytically self-cleaning hamburger-structured nanofiber membrane for protein separation comprises a base membrane, a photocatalytically self-cleaning functional layer, and a high-flux functional layer, and specifically includes the following steps: (1) Preparation of photocatalytic self-cleaning high-throughput functionalized hamburger structure nanofiber membrane spinning solution for protein separation and purification: The spinning solution is prepared by three materials according to the following component mass percentages: The first material is 11-15% substrate, 6-10% TPU, and the remainder is solvent; the substrate is dissolved in the solvent and heated and stirred, and after dissolution, TPU is added and stirred for 3-5 h until completely dissolved; The second material is 11-15% substrate, 6-10% TPU, 0.6-1% polyphenol modifier, and the remainder is solvent; the polyphenol modifier is dissolved in the solvent and heated and stirred, and after dissolution, the substrate and TPU are added and heated and stirred for 1.5-3.5 h until completely dissolved; The third material is 11-15% substrate, 6-10% TPU, 0.1-0.5% C3N4, and the remainder is solvent; the C3N4 is dissolved in the solvent and heated and stirred, and after dissolution, the substrate and TPU are added and heated and stirred for 1.5-3.5 h until completely dissolved; (2) Preparation of photocatalytic self-cleaning high-throughput functionalized hamburger-structured nanofiber membranes for protein separation and purification: The spinning solution in step (1) was spun into a membrane using microfluidic electrospinning. The DC voltage of the spinning machine was set to 16-20 KV, the flow rate of the injection pump was 1.1-1.5 ml / h, and the receiving distance was 16-20 cm. The membrane preparation process involved three strands of material being spun sequentially. The first strand of material was 4-6 ml, and the nanofiber substrate was spun for 3-5 h to form a membrane with a thickness of 55-75 μm. Then, the second strand of spinning solution, 2-4 ml, was quickly spun on the membrane to form a polyphenol-modified nanofiber membrane for 1.5-3.5 h. The thickness of the two membrane layers was 90-130 μm. Similarly, the third strand of material was 2-4 ml, and the polyphenol-g-C3N4 nanofiber membrane was spun for 1.5-3.5 h to form a polyphenol-g-C3N4 nanofiber membrane. The total membrane thickness was 110-145 μm, and the membrane pore size was 0.3-0.8 μm. μm; (3) Evaluation of photocatalytic self-cleaning performance: After the protein separation experiment, the membrane was placed in a 1-5 wt.% sodium sulfate solution and stirred. At the same time, it was subjected to photocatalytic degradation of surface organic matter under a 100-750 W xenon lamp for 0.5-2.5 h. The flux recovery rate was 95%-100%.
2. The preparation method according to claim 1, characterized in that, The synthesis of C3N4: Weigh 20-40 g of nitrogen-containing organic matter and place it in a 150-250 ml covered alumina crucible. In a muffle furnace, heat the mixture at 6-10 °C for 1 min. -1 The heating rate was increased to 550-650 °C in air atmosphere and held for 2-6 h. After calcination, the mixture was cooled to room temperature to obtain a light yellow C3N4. The C3N4 powder was then thoroughly ground in an agate mortar and sealed for storage.
3. The preparation method according to claim 1, characterized in that, The spinning solution is prepared by selecting one or more of the following polyphenolic modifiers: tea polyphenols, pyrogallol, and tannic acid.
4. The preparation method according to claim 1, characterized in that, The spinning solution is prepared by using one of the following as the base material: polyvinylidene fluoride, polyethersulfone, or polyacrylonitrile.
5. The preparation method according to claim 1, characterized in that, The spinning solution is prepared by using one of the following solvents: N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone.
6. The preparation method according to claim 2, characterized in that, The nitrogen-containing organic compounds used to synthesize C3N4 modifiers are one or more of melamine, thiourea, dicyandiamine, and urea.
Citation Information
Patent Citations
A light-driven single-layer Janus oil-water separation membrane and preparation method thereof
CN115646221B
Preparation method of a moth-eye structure bionic photocatalytic self-cleaning oil-water separation membrane
CN115970520B
Porous solvent cast film without compact epidermal layer as well as preparation method and application of porous solvent cast film
CN117384420A
Super-hydrophilic self-cleaning oil-water separation membrane as well as preparation method and application thereof
CN109847598A
Self-cleaning oil-water separation membrane as well as preparation method and application thereof
CN116159447A
